Film Bilal : A New Breed Of Hero: Analisis Narasi Perspektif Branston & Stafford - Masrul, Khaisar; Adrianda, Irsan (BINA' AL-UMMAH, 2021)
Film is a form of mass communication that is dominant today because it is many and easy for many people to see. In the story film there is also a narrative element. Bilal: A New Breed Of Hero is the first religious animated film based on the story of the Prophet's best friend Bilal bin Rabbah. But in this film also reaped controversy because in this film the Islamic narrative is made to be more vague so that the film also gets rejected. Based on this context, the purpose of this paper is to answer major and minor questions. The major question is how to analyze the film's narrative. Then the first minor question, the general theory of what narrative can be used to analyze the film. Second, what kind of plot is depicted in the film. Third, in what kind of different medium is the narrative of the film? In this paper the concept used to analyze the narrative of the film is a general theory of narrative, storyline or plot and narrative in different media according to the perspective of Braston and Stafford chapter narrative (2010). The results of the analysis obtained in the general theory of narrative can be applied narrative theory for example that was triggered by Prop and Todorov in the film. The narrative about Bilal in addition to the form of film is also delivered in the form of comic strips and animation.